Exploring the potential of electronic magazine among internet users - Kamarulzaman, Y.; Madun, A.; Che Azmi, A.A. (Academic Journals, 2010)
This preliminary study explores the potential of online magazine or electronic magazine (e-magazine) in the context of Malaysia. Although many well-known large print-publishers now have their own version of electronic magazines, it is found that most of these publishers are foreign-based, while local-based electronic magazines are virtually none existed. Based on a survey among internet users in Malaysia, the study finds that there is a potential market for electronic magazine. Due to the supporting infrastructure for online transactions which is still at infancy stage in this country, it is recommended that local publishers should embark e-magazine project as a supplementary to the print version not as a stand-alone product.